Occurrence and multilocus genotyping of Giardia duodenalis in pets and zoo animals in Shanghai, China - Liu, Hua; Shen, Yujuan; Liu, Aiqin; Yin, Jianhai; Yuan, Zhongying; Jiang, Yanyan; Pan, Wei; Zhang, Yumei; Zhao, Wei; Cao, Jianping (The Journal of Infection in Developing Countries, 2017)
Introduction: High prevalence of Giardia infections occurs in humans and animals, partly because of the increasing numbers of pets. We determined the presence and genotypes of G. duodenalis in pets and zoo animals. Methodology: A total of 84 specimens were collected from dogs and cats from a pet hospital, and 54 specimens from a zoo, which included deer, tigers, yaks, and others. All the specimens were examined by microscopy and by polymerase chain reaction (PCR) amplification and subsequent sequencing of glutamate dehydrogenase (gdh), beta-giardin (bg), and triose phosphate isomerase (tpi) genes. Results: Giardia infection was confirmed in 5.95% and 15.48% of animals by microscopy and by PCR, respectively; the detection levels were 13.33% and 26.67% for pets, and 1.85% and 9.26% for zoo animals. Four assemblages were identified: assemblage C in dogs, cats, and a sheep; D in dogs, a wolf, a yak, and a leopard; E in a sheep; and F in a cat and a leopard. PCR gave the highest amplification rate at the gdh locus. Eight, five, and four sequences were novel at the gdh, bg, and tpi loci, respectively. Two tpi sequences of dog-derived assemblage C had 100% homology with amino acid sequences from human-derived isolates. Conclusions: The molecular characterization of G. duodenalis in pets and zoo animals in China is described. Assemblage D was identified in a yak and a leopard for the first time. Multilocus genotyping analysis identified the same tpi gene sequences of assemblage C in dogs and humans, indicating potential zoonotic transmission.